Flexible load management using flexibility bands. (1st July 2022) - Saavedra, Aldo; Negrete-Pincetic, Matias; Rodríguez, Rafael; Salgado, Marcelo; Lorca, Álvaro
Abstract: The large integration of variable renewable energy sources brings new challenges to system operations due to their volatile nature. In this context, demand response programs appear as an important alternative to match the instantaneous supply and demand of energy by changing the electric use of end-users. The traditional load control schemes of demand response are the direct and indirect control. While the direct schemes assure coordination and fail in scalability, the indirect schemes assure scalability, but they could fail in coordination. To face some of the challenges, this paper defines a framework and mathematical formulation for the interactions between a demand aggregator and its end-users, based on flexibility bands. It allows the aggregator to communicate and control a higher number of end-users at the same time that the end-users can make local decisions regarding their consumption. The flexibility band is a control signal, composed of an upper and a lower consumption bound, so that end consumers can consume electricity in the way they want as long as they stay within these bounds. The band features can be linked to contractual arrangements allowing the creation of new products for electricity markets. The simulations consider an aggregator interacting with 10000 end-users. The end-users present different types of flexible loads, such as thermal, deferrable, and non-interruptible loads. The results indicate that this scheme is capable of achieving scalability and coordination, and it has the potential to provide new services such as adjusting the flexibility bands after the first response from end-users. Highlights: Developing of a scheme that allows the scalable control of flexible electrical loads. Implementation of flexibility bands for information exchange between DR players. Proposal of a scalable and low-information aggregator model. Developing a methodology for tuning flexibility bands into contractual arrangements.